Strategies to Strengthen Teacher Professionalism Through Competency Development - Fatma Yulita; Deslina Fitri; Muhamad Yahya (Al Bahri: Journal of Islamic Education, 2025)
Education is the main foundation in nation building, and teachers play a strategic role in creating a quality learning process. The professionalism of teachers greatly determines the success of education, especially in facing the challenges of globalization and technological developments. This article aims to examine the importance of teacher competency development as a strategy to strengthen professionalism in improving the quality of education. This study uses a qualitative approach through the literature review method by examining various academic sources, government policies, and related research results. The results of the study show that the development of teachers' competencies, both pedagogical, personality, social, and professional, must be carried out in a systematic, structured, and sustainable manner. Some of the strategies identified include individual training, observation and reflection, involvement in curriculum development, as well as scientific forums and professional organizations. Programs such as pre-service education, in-service training, as well as reinforcement through teacher working groups (MGMP) and classroom action research are integral to this process. With comprehensive competency development, teachers are expected to be able to become adaptive, innovative, and professional educators in facing today's educational dynamics.